Analysis of Received Signal Strength under Handoff Condition using Network Simulator 2 - Saxena, Shivi; Kumar, Arun (International Journal of Computer Sciences and Engineering, 2018)
Wireless communication involves a wide variety of technologies, services and applications, developed to satisfy the user’s specific needs in variety of deployment scenarios. The cellular phones are one of the examples of wireless communication application. Globally, the cellular networks have progressed from a simple first generation to fourth generation and probably will be progressing to fifth generation by the end of 2019. Though there is an appreciable progress in the high speed data with the generation, the problem in the voice call still persists, particularly when in motion, due to the continuous changes in the receiving signal. This article aims at improving the QoS by implementing the tele-traffic pattern proposed in earlier 90’s by Steele and Nofal to manage the hand-off mechanism in order to reduce the voice and data degradation during motion and simulating same using Network Simulator 2 for validation. The results of the experimental analysis show that the hand off degradation of voice and data is reduced by the implementation of the said tele-traffic pattern. Hence, proving the proposed energy detection technique on the Steele and Nofal traffic model to be best suited for the handoff situation.